The R.E.N.A.L score's relevance in determining perioperative and oncological outcomes: a Middle-Eastern tertiary care center experience. Issue 3 (3rd July 2022) - Abou Heidar, Nassib; Hakam, Nizar; El-Asmar, Jose M; Najdi, Jad; Khauli, Mark A.; Degheili, Jad; El-Hajj, Albert; Nasr, Rami; Wazzan, Wassim; Bulbul, Muhammad; Mukherji, Deborah; Khauli, Raja
ABSTRACT: Objective: The aim of this study is to evaluate the significance of the R.E.N.A.L nephrometry scoring system in predicting perioperative and oncological outcomes and determining the surgical approach of choice for kidney tumors. Patients and Methods: Our study retrospectively reviewed outcomes from the year 2002 to 2017. Mann-Whitney U test was used to compare continuous variables and chi-square test was used to compare categorical variables. Kaplan-Meier estimates and multivariable cox proportional hazard regression were performed to determine an association between the different R.E.N.A.L categories and disease recurrence or mortality. Results: A total of 325 patients underwent kidney surgery The most common R.E.N.A.L score category in our cohort study was intermediate (41.2%), followed by low, (33.2%) and high (25.5%). Patients with a high R.E.N.A.L score had worse perioperative outcomes compared to those with a low R.E.N.A.L score. High R.E.N.A.L score patients were 3 times more likely to receive blood transfusions compared to those with a low R.E.N.A.L score (19.4% vs 6.3%, p = 0.018), and a statistically significant longer hospital length of stay was also observed between the two groups (median 4.5 vs 4 days, p = 0.0419). In addition, the only predictor of disease recurrence or mortality was a high R.E.N.A.L score (Hazard Ratio (HR) 3.65, 95% Confidence Interval (CI) 1.05–12.7, p = 0.041). Conclusion: Our study sheds light on the use of R.E.N.A.L nephrometry score in predicting perioperative, postoperative, and oncological outcomes. Such findings may play a role in optimizing surgical approaches and pre-operative patient counseling.